2016
DOI: 10.1155/2016/6057434
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of Flavonols Quercetin, Myricetin, and Kaempferol in the Sri Lankan Tea (Camellia sinensisL.) and Their Health-Promoting Aspects

Abstract: Flavonol glycosides in tea leaves have been quantified as aglycones, quercetin, myricetin, and kaempferol. Occurrence of the said compounds was reported in fruits and vegetable for a long time in association with the antioxidant potential. However, data on flavonols in tea were scanty and, hence, this study aims to envisage the flavonol content in a representative pool of accessions present in the Sri Lankan tea germplasm. Significant amounts of myricetin, quercetin, and kaempferol have been detected in the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 45 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…The last two peaks were identified as rutin and myricetin, respectively. The presence of rutin in tea was reported previously by Pękal et al (2011), while Jeganathan et al (2016) reported the presence of myricetin. Furthermore, several other unidentifiable peaks in the studied sample.…”
Section: Phenolic Compounds Identification Using High Performance Liqsupporting
confidence: 64%
“…The last two peaks were identified as rutin and myricetin, respectively. The presence of rutin in tea was reported previously by Pękal et al (2011), while Jeganathan et al (2016) reported the presence of myricetin. Furthermore, several other unidentifiable peaks in the studied sample.…”
Section: Phenolic Compounds Identification Using High Performance Liqsupporting
confidence: 64%
“…In this study, chromatographic analysis of the FF obtained from the BBE of P. vulgaris L., identified three molecules tea plant (C. sinensis L.) from Sri Lanka but at different concentrations (0.94 mg/g, 1.5 mg/g, and 1.31 mg/g, respectively) 25 ; this plant has been reported to have antioxidant, antimicrobial, anticancer, anti-atherosclerotic, and anti-proliferative properties.…”
Section: Discussionmentioning
confidence: 92%
“…Different kinds of flavonoids were reported in different types of tea in the related studies. The most common flavonoids aglycones in Sri Lankan tea were quercetin, myricetin, and kaempferol (Jeganathan et al, ). In our study, flavonoids quercetins were main compounds found in black tea infusion waste.…”
Section: Resultsmentioning
confidence: 99%